Design of a Microstrip Antenna for Breast Cancer Detection - Kaschel-Carcamo, H (Institute of Electrical and Electronics Engineers Inc., 2021)
This paper present the design of a microstrip patch antenna at 3.5 GHz band for breast cancer detection for WBAN applications. Wireless Body Area Network (WBAN) applications are very useful for monitoring patient health and transmitting data wireless. WBAN can benefit greatly from wearable antennas. WBAN can benefit greatly from portable antennas. The design of the antenna with a quarter lambda patch and ground plane with a Taconic RF-35 dielectric substrat with a dielectric constant of 3.5. The simulation of the antenna with the breast model with or without tumor to obtain the levels of Return Loss, VSWR, Gain, Radiation pattern, Power Loss Density and the levels of SAR. The evaluation of the maximum SAR levels with breast model and increased antenna distance to analyze results of the sidseign parameters, which are in accordance with the standards currently accepted. © 2021 IEEE.